Sources and outcomes of grocery retailer brand equity: a study towards a unified brand equity model in the South African grocery industry - Pwaka, Oliver (My University, 2021)
Globally, the top 250 grocery retailers’ aggregate sales revenue reached US $4.53 trillion in 2018, making contributions to employment and GDP. In South Africa, about nine percent sector contribution to the overall GDP is made by the grocery retailer industry. Despite the micro, macro and international environmental challenges that businesses face, the South African grocery retailer industry is expanding its footprints into other African countries. Typically, Shoprite, which was one of the leading grocery retailer brands in 2016, had a massive network of 2276 outlets of which 316 of these outlets were located regionally outside the South African borders. An analysis of the SPAR brand similarly shows that it has13,500 stores located in 35 counties across various continents. The Pick n Pay brand has 1 795 stores across the African Continent. Even though Woolworths South Africa has less stores -712 stores in South Africa and in 10 African countries, it was the 2019 number 11 top South African most valuable brands and the number 1 most valuable grocery retailer brand in the country. Woolworths South Africa (SA) has therefore become a powerhouse brand. In 2019 for example, Woolworths’ brand value was $1.1 trillion. This thus placed Woolworths SA as the number 1 most valued grocery retailer brand in South Africa. The sources and outcomes of Woolworths high brand value or brand equity needed examination. The current generic brand equity models do not accommodate retailer industry specific characteristics. It is reported that the most commonly used customer-based brand equity (CBBE) models such as the Aaker’s (1991) and Keller’s (1993) CBBE models measuring sources of brand equity are too abstract, simplistic, generic and fail to incorporate retail-specific dimensions. Furthermore, these CBBE models do not provide brand equity outcomes. To examine the underlying sources and outcomes of retailer brand equity, there was need to integrate both the retailer specific aspects or dimensions with the classical brand equity models. Thus, the objectives of this study was to integrate elements of Aaker’s (1991) CBBE model, Yoo and Donthu’s (2002) model, Jara and Cliquet’s (2012) retail brand equity model, Buil et al.’s (2013) CBBE customer response model, and Anselmsson, Burt and Tunca’s (2017) retailer brand equity model to develop a unified grocery retailer equity model for the examination of the sources (brand awareness, brand image, retailer sincerity, retailer excitement, retailer competence, perceived quality, customer service, price, trust, distribution, brand loyalty), and customer-based outcomes (brand preference and repurchase intention) of Woolworths’ brand equity in the South African grocery retailer sector. Data was quantitatively collected from 480 South African consumers in all age (18-65 years old) and racial groups, financial and educational backgrounds. The data was analysed with the SMARTPLS-Structural Equation Modelling (SEM). After testing and confirming the measurement model (outer model), which assesses construct reliability, validity and model fit, the structural model (inner model) was used to test the hypotheses. The results revealed that after brand awareness significantly impacts customer brand excitement, perceived quality, brand image, brand loyalty, and the loyalty is significantly impacted by price, trust and distribution, it in turn strongly and significantly drives brand equity. The sources that directly impacted Woolworths’ brand equity were brand excitement, brand awareness and loyalty, while perceived quality and brand image did not. The significant outcomes of brand equity were the hypothesized brand preference and repurchase intention. A test of mediation revealed that brand equity mediated the relationships between brand awareness, customer brand excitement, brand loyalty and brand preference. Brand equity also mediated in the relationships between brand awareness, customer brand excitement, brand loyalty and repurchase intention. The unified model explained 60.3% of brand loyalty, 61.1% of brand equity, 71.7% of brand preference and 54.2% of repurchase intention. These are all strong explanatory powers, especially in in a consumer behaviour study. Theoretically, the developed and tested unified conceptual model can be used by other retailers to examine the sources and outcomes of their brand equity. Practically the identified brand equity sources and outcomes can guide grocery retailer brand management on ways to enhance both customer and retailer value
A thesis submitted to the School of Business Sciences, Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy (in Marketing), 2021